2019
DOI: 10.1167/tvst.8.5.9
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Study of Chemical Composition, Molecular and Rheological Properties of Silicone Oil Medical Devices

Abstract: PurposeWe evaluated chemical composition, and molecular and rheological properties in 10 commercially available silicone oils (SilOils), focusing on siloxane chains of low molecular weight (LMW components, LMWC) that are known to be “impurities” produced during the SilOil synthesis process.MethodsWe assessed the type of SilOil polymer and molecular weight distribution (MWD) by spectroscopy and conventional size exclusion chromatography, respectively. From the Cumulative MWD, we calculated the fractions of LMWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The common standards regarding these impurities have not been established during the production and disclosure of information by manufacturers [ 26 ]. Mendichi et al and Dresp have both shown that different brands of commercially available ophthalmic SilOils contain varying amounts of LMWCs [ 27 , 28 ]. Furthermore, LMWCs have been reported to be the most abundant component by weight in all chemical impurities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common standards regarding these impurities have not been established during the production and disclosure of information by manufacturers [ 26 ]. Mendichi et al and Dresp have both shown that different brands of commercially available ophthalmic SilOils contain varying amounts of LMWCs [ 27 , 28 ]. Furthermore, LMWCs have been reported to be the most abundant component by weight in all chemical impurities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the building blocks in the polymerisation of SilOil, cyclic LMWCs have a much higher content than their linear counterparts in commercially available SilOils [ 28 ]. Therefore, the presence of cyclic LMWCs in SilOil may be the key risk factor leading to cytotoxicity, which should be taken into consideration in future testing and purification regimes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 4 9-12 In addition, it was recently reported that the quality of silicone oil medical products varied from batch to batch even under the same brand name, and that they may be toxic. [13][14][15] It has also been reported that unexplained visual impairments occurred from damages to retinal structures in eyes treated with SOT. [16][17][18] There are also reports that eyes with non-complex RD treated by SOT had poorer postoperative retinal sensitivity and visual acuity than eyes treated by GT.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that the nominal η refers to the dominant fraction of PDMS polymers of the desired length, but, despite post-synthesis purification processes, the final SO is a mixture of this fraction and a variable amount of siloxane chains of lower and higher MW [ 41 ]. Indeed, commercially available SO with the same declared η can vary significantly in terms of real η value, MW distribution and relative content of low molecular weight compounds (LMWC) [ 42 , 43 ]. In particular, LMWC, short-chain siloxane oligomers or polymers, have long been investigated due to their potentially harmful properties, being able to act as emulsifiers of SO and to diffuse from the vitreous cavity into ocular tissues [ 44 ].…”
Section: Structural and Physico-chemical Findingsmentioning
confidence: 99%